The State of Knowledge Extraction from Text for Thai Language - Netisopakul, Ponrudee; Wohlgenannt, Gerhard (My University, 2017)
With the emergence of the Semantic Web (or Linked Data), increased efforts have been made to automatically extract formalized semantic knowledge from natural language text. Most research work and tools for knowledge extraction are focusing on text in English language. In this work, wepresent our research-in-progress on evaluating the state-of-the-art in knowledge extraction from text for Thai language. For this purpose, we investigate the existing knowledge extraction literature and group the available research work and tools into eight knowledge extraction tasks. Our preliminary results from the survey of the state-of-the-art show that there exist large research gaps and therefore future research opportunities in Thaiknowledge extraction, and we provide hints for available research directions.
Keywords: Knowledge extraction; Landscape analysis; Thai language text